Methamphetamine-Induced Psychosis Is Associated With DNA Hypomethylation and Increased Expression of AKT1 and Key Dopaminergic Genes - Nohesara, Shabnam (Am J Med Genet B Neuropsychiatr Genet, 2016)
Methamphetamine, one of the most frequently used illicit drugs worldwide, can induce psychosis in a large fraction of abusers and it is becoming a major problem for the health care institutions. There is some evidence that genetic and epigenetic factors may play roles in methamphetamine psychosis. In this study, we examined methamphetamine-induced epigenetic and expression changes of several key genes involved in psychosis. RNA and DNA extracted from the saliva samples of patients with methamphetamine dependency with and without psychosis as well as control subjects (each group 25) were analyzed for expression and promoter DNA methylation status of DRD1, DRD2, DRD3, DRD4, MB-COMT, GAD1, and AKT1 using qRT-PCR and q-MSP, respectively. We found statistically significant DNA hypomethylation of the promoter regions of DRD3 (P=0.032), DRD4 (P=0.05), MB-COMT (P=0.009), and AKT1 (P=0.0008) associated with increased expression of the corresponding genes in patients with methamphetamine psychosis (P=0.022, P=0.034, P=0.035, P=0.038, respectively), and to a lesser degree in some of the candidate genes in nonpsychotic patients versus the control subjects. In general, methamphetamine dependency is associated with reduced DNA methylation and corresponding increase in expression of several key genes involved in the pathogenesis of psychotic disorders. While these epigenetic changes can be useful diagnostic biomarkers for psychosis in methamphetamine abusers, it is also consistent with the use of methyl rich diet for prevention or suppression of psychosis in these patients. However, this needs to be confirmed in future studies.